Sexual assault in Ballari, Karnataka, India: A four year retrospective review - Charan Kishor, Shetty; Gururaj, Biradar; Pavanchand, Shetty (2017)
Sexual assault is both a common and a very serious crime which is investigated by the police with an intensity second only to that of murder. Despite India stiffening its laws on sexual crimes, nothing much has changed on the ground. The present study aimed to reveal the socio demographic aspects of sexual assault in Ballari, Karnataka, India. This retrospective study was conducted on 86 cases of sexual assault received for examination at Vijayanagara institute of medical sciences(VIMS), Ballari, Karnataka, from 2010 - 2013. This study revealed that incidences of sexual assault were were higher in 2011 compared to 2013. It also re-vealed that the most vulnerable age group was 11-20 years. Most commonly, sexual crimes were performed by a person familiar to the victim (33.72%). Most victims were medico-legally examined on the second day (46.51%) after the assault. Recent tear of hymen was noticed in 16.66% of female victims. Restrain marks on the victims were present in 25 (29.06%) cases. The study may help to enhance public awareness regarding sexual violence. It may also help the law enforcement authorities implement strategies to make the society a safer place.